Three warm jupiters around solar-analog stars detected with TESS* - Eberhardt, Jan; Hobson, Melissa J.; Henning, Thomas; Trifonov, Trifon; Brahm, Rafael; Espinoza, Nestor; Jordán, Andrés; Thorngren, Daniel; Burn, Remo; Rojas, Felipe I.; Sarkis, Paula; Schlecker, Martin; et al. (The astronomical journal)
We report the discovery and characterization of three giant exoplanets orbiting solar-analog stars, detected by the TESS space mission and confirmed through ground-based photometry and radial velocity measurements taken at La Silla observatory with FEROS. TOI-2373 b is a warm Jupiter orbiting its host star every ∼13.3 days, and is one of the most massive known exoplanet with a precisely determined mass and radius around a star similar to the Sun, with an estimated mass of m p = and a radius of r p = . With a mean density of , TOI-2373 b is among the densest planets discovered so far. TOI-2416 b orbits its host star on a moderately eccentric orbit with a period of ∼8.3 days and an eccentricity of e = . TOI-2416 b is more massive than Jupiter with m p = , however is significantly smaller with a radius of r p = , leading to a high mean density of . TOI-2524 b is a warm Jupiter near the hot Jupiter transition region, orbiting its star every ∼7.2 days on a circular orbit. It is less massive than Jupiter with a mass of m p =, and is consistent with an inflated radius of r p =, leading to a low mean density of . The newly discovered exoplanets TOI-2373 b, TOI-2416 b, and TOI-2524 b have estimated equilibrium temperatures of K, K, and K, respectively, placing them in the sparsely populated transition zone between hot and warm Jupiters.
Veröffentlicht: 29. November 2023
Gesehen am 28.06.2024